GxE interaction on cashew (Anacardium occidentale L.) cultivar productivity components in Benin - Ezin, Vincent Awe (My University, 2019)
The aim of this study was to compare the behavior of different cashew in two environments in Benin over a period of four years. The study consisted of monitoring the phenology and productivity of four cashew genotypes during four consecutive cropping seasons (2013-2014; 2014-2015; 2016-2016 and 2016-2017) in the villages of Adourékoman, and Founga. These four cashew genotypes were selected according to their agro-morphological characteristics. A total of 36 trees were used in an experimental design laid at randomized complete block in each site for data collection. Phenology of the tree and yield components were the data collected and submitted to analysis of variance (ANOVA), additive main effects and multiplicative interaction (AMMI), heritability, stability and Pearson correlation using ARiS software. The results of the variance analysis of the phenology and reproductive data showed a significant (P<0.05.) influence of environment on the cashew’s parameters studied. The results also showed that North-west presented the higher nut weight (5.83 kg/tree) compared to the Central (1.67 kg/tree) region and the highest nut weight was recorded intree with small fruit and red colour (M2R). The lowest nut weight was observed in the Centre with the genotype having big fruit and yellow colour (M1Y) (1.53 kg/tree). However, the most stable genotype in the two environments was the genotype having big fruit and yellow colour (M1Y). The nut and apple circumference were positively and highly correlated (r=0.616; P<0.001). There were significant differences in rankings of the genotypes at the two environments for all variables. The phenology and reproductive data revealed a significant influence of environment on cashew parameters studied. It was recommended to undertake hybridization between M2R with another variety of cashew for the improvement of cashew productivity in Benin.
Keywords: AMMI; Cashew; phenology; phenotype; heritability; stability; performance